Expression of placenta-specific 1 and its potential for eliciting anti-tumor helper T-cell responses in head and neck squamous cell carcinoma. (1st January 2021) - Hayashi, Ryusuke; Nagato, Toshihiro; Kumai, Takumi; Ohara, Kenzo; Ohara, Mizuho; Ohkuri, Takayuki; Hirata-Nozaki, Yui; Harabuchi, Shohei; Kosaka, Akemi; Nagata, Marino; Yajima, Yuki; Yasuda, Syunsuke; et al.
ABSTRACT: Placenta-specific 1 (PLAC1) is expressed primarily in placental trophoblasts but not in normal tissues and is a targetable candidate for cancer immunotherapy because it is a cancer testis antigen known to be up-regulated in various tumors. Although peptide epitopes capable of stimulating CD8 T cells have been previously described, there have been no reports of PLAC1 CD4 helper T lymphocyte (HTL) epitopes and the expression of this antigen in head and neck squamous cell carcinoma (HNSCC). Here, we show that PLAC1 is highly expressed in 74.5% of oropharyngeal and 51.9% of oral cavity tumors from HNSCC patients and in several HNSCC established cell lines. We also identified an HTL peptide epitope (PLAC131-50 ) capable of eliciting effective antigen-specific and tumor-reactive T cell responses. Notably, this peptide behaves as a promiscuous epitope capable of stimulating T cells in the context of more than one human leukocyte antigen (HLA)-DR allele and induces PLAC1-specific CD4 T cells that kill PLAC1-positive HNSCC cell lines in an HLA-DR-restricted manner. Furthermore, T-cells reactive to PLAC131-50 peptide were detected in the peripheral blood of HNSCC patients. These findings suggest that PLAC1 represents a potential target antigen for HTL based immunotherapy in HNSCC.